Analysis of students’ mathematical communication skills in web-based geometry in space and plane learning - Priatna, Nanang; EfridaMuchlis, Effie; Maizora, Syafdi (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2022)
Mathematical communication skill in a mathematics learning process isa basic skill that must be possessed by students in developing the ability to think, reason, and solve problems. Especially in virtual learning, both online learning and blended learning, teachers must be able to conduct learning that built students' mathematical communication skills. Implementing web-based geometry in space and plane learning can be an alternative for forming mathematical communication skills with the aid of technology in today's virtual learning environment. This research aimed to examine 1) how web-based geometry in space and plane learning is implemented, 2) how students' mathematical communication skills are built through web-based geometry in space and plane learning, and 3) what learning alternatives need improvement to optimize students' mathematical communication skills. This research used a qualitative method with instruments in the form of lecturer activity observation sheet, student activity observation sheet, interview guide, and mathematical communication skills test. Data were collected through observation of learning implementation, mathematical communication skills testing, and interviews based on the test results. The data were analyzed with a descriptive technique. The results showed that 1) web-based geometry in space and field learning can be implemented by exploring with concept discussion on the activity pages, 2) web-based geometry in space and plane learning could help students explore ideas throughout the students' mathematical communication skills formation process, and 3) the learning could be improved by developing an HLT (hypothetical learning trajectory) using technology to develop a higher level of mathematical thinking ability.